Determinants of Health Care Renunciation among Women in Ivory Coast: Case of the District of Abobo Anonkoi-3 - Jérôme Kouame; Julie-Ghislaine Sackou-Kouakou; Marie-Laure Tiade; Régine Attia-Konan; Madikiny Coulibaly; Aïssata Dagnogo; Kouame Koffi; Mariette Gokpeya; Simone Malik; Angèle Desquith; Agbaya Oga; Kouakou Luc; Kouadio Kouadio (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Health care renunciation aims to identify unmet care needs that a health condition would have justified. This behavior appears to be more common in women than in men. The objective of this work was to analyze the determinants of the health care renunciation among women in the city of Abidjan.Subjects and Method: We carried out a cross-sectional study from March to May 2019 in Anonkoi-3, a peri-urban district of the municipality of Abobo, in the north of the city of Abidjan. Questionnaires served to collect informations. Bivariate analyzes and a multiple logistic regression were used to measure the association between the different types of renunciation and the characteristics of women. Dependant variable was healthcare renunciation. Independent variables were socio-demographic, economic, health status characteristics and reasons for renouncing to health care.Results: The population sample consisted of 423 women (with mean age= 32; SD= 12 years). The renunciation on consultations with the general practitioner concerned, 72.34% of women. Regarding consultation with the specialist, the ophthalmologist (25.05%), the dentist (21.99%), and the gynecologist (14.89%) were those mostly renounced by the women. After consultation, 31.2% of them renounced to pursuing other treatment. They most often renounced to buying drugs from conventional medicine (19.62%) and preferred to use street drugs and traditional drugs (87.71%). All things being equal, women aged 28 to 38 (OR= 2.45; 95% CI= 1.31 to 4.68; p= 0.013), artisans and traders (OR= 3.22; 95% CI= 1.48 to 7.38; p= 0.004) and those in trade learning (OR= 2.42; 95% CI= 1.12 to 5.49; p= 0.028) significantly renouncing more on health care.Conclusion: In addition to financial reasons, the renunciation on health care can be explained by individual and social behaviors specific to individuals.Keywords: women, healthcare renunciation, precariousness, social inequalities, ivory coastCorrespondence: Jérôme Kouame, Faculty of Pharmaceutical and Biological Sciences, Department of Public Health, Hydrology and Toxicology, University Félix Houphouët Boigny, BPV 34 Abidjan 01, Ivory Coast. Email: jerome.kouamejj@gmail.com. Mobile: 0022565237900.Journal of Health Policy and Management (2021), 06(02): 116-129https://doi.org/10.26911/thejhpm.2021.06.02.04